Determinants of mortality in a large group of hemodialysis patients hospitalized for COVID-19 - (:unkn) unknown (BMC, 2021)
Background: Maintenance hemodialysis (MHD) patients are at increased risk for coronavirus disease 2019 (COVID-19). The aim of this study was to describe clinical, laboratory, and radiologic characteristics and determinants of mortality in a large group of MHD patients hospitalized for COVID-19. Methods: This multicenter, retrospective, observational study collected data from 47 nephrology clinics in Turkey. Baseline clinical, laboratory and radiological characteristics, and COVID-19 treatments during hospitalization, need for intensive care and mechanical ventilation were recorded. The main study outcome was in-hospital mortality and the determinants were analyzed by Cox regression survival analysis. Results: Of 567 MHD patients, 93 (16.3%) patients died, 134 (23.6%) patients admitted to intensive care unit (ICU) and 91 of the ones in ICU (67.9%) needed mechanical ventilation. Patients who died were older (median age, 66 [57-74] vs. 63 [52-71] years, p = 0.019), had more congestive heart failure (34.9% versus 20.7%, p = 0.004) and chronic obstructive pulmonary disease (23.6% versus 12.7%, p = 0.008) compared to the discharged patients. Most patients (89.6%) had radiological manifestations compatible with COVID-19 pulmonary involvement. Median platelet (166 x 10(3) per mm(3) versus 192 x 10(3) per mm(3), p = 0.011) and lymphocyte (800 per mm(3) versus 1000 per mm(3), p < 0.001) counts and albumin levels (median, 3.2 g/dl versus 3.5 g/dl, p = 0.001) on admission were lower in patients who died. Age (HR: 1.022 [95% CI, 1.003-1.041], p = 0.025), severe-critical disease clinical presentation at the time of diagnosis (HR: 6.223 [95% CI, 2.168-17.863], p < 0.001), presence of congestive heart failure (HR: 2.247 [95% CI, 1.228-4.111], p = 0.009), ferritin levels on admission (HR; 1.057 [95% CI, 1.006-1.111], p = 0.028), elevation of aspartate aminotransferase (AST) (HR; 3.909 [95% CI, 2.143-7.132], p < 0.001) and low platelet count (< 150 x 10(3) per mm(3)) during hospitalization (HR; 1.864 [95% CI, 1.025-3.390], p = 0.041) were risk factors for mortality. Conclusion: Hospitalized MHD patients with COVID-19 had a high mortality rate. Older age, presence of heart failure, clinical severity of the disease at presentation, ferritin level on admission, decrease in platelet count and increase in AST level during hospitalization may be used to predict the mortality risk of these patients.
Keywords: Hemodialysis; COVID-19; Radiological manifestations; Mortality; Clinical findings; KIDNEY-DISEASE; CORONAVIRUS; OUTCOMES; INFECTION